2023
DOI: 10.1136/bmjgh-2023-012358
|View full text |Cite
|
Sign up to set email alerts
|

Implementation research for developing Civil Registration and Vital Statistics (CRVS) Systems: lessons from Indonesia

Abstract: Civil Registration and Vital Statistics (CRVS) systems are the optimal source for data on births, deaths and causes of death for health policy, programme evaluation and research. In Indonesia, indicators such as life expectancy at birth, childhood and maternal mortality rates and cause-specific death rates need to be routinely monitored for national health policy. However, the CRVS system is not yet producing reliable vital statistics, which creates a challenge for evidence-based health action. In 2019, the In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Developing a scalable district level model will require adopting or adapting these resources to the Indian context. This will need formative and implementation research at district level as demonstrated in Indonesia,[ 20 ] where the formative research guided the feasibility of implementation through local adaptation of international standard protocols, training resources, and capacity building programs for different stakeholders. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…Developing a scalable district level model will require adopting or adapting these resources to the Indian context. This will need formative and implementation research at district level as demonstrated in Indonesia,[ 20 ] where the formative research guided the feasibility of implementation through local adaptation of international standard protocols, training resources, and capacity building programs for different stakeholders. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%